Analysis of the data in qualitative research: an eye-glance at the morse and field proposal - Teixeira, Marizete Argolo; Nitschke, Rosane Gonçalves; Paiva, Mirian Santos (Rev Rene, 2008)
This is a report of an experience deeply experienced during the analysis of data in qualitative research in a dissertation. The aim was to contribute with refl exion on the subject matter. The stage of analysis of the data represents the invisible side in the qualitative investigation, once in general, the phase of analysis of the data represents the invisible face of the qualitative investigation, a time when in general, the researchers do not provide enough information to the reader concerning the way they can change data into interpretation to be supported theoretically on the basis of the adopted epistemological principles. When adopting the proposal of Morse and Field for analysis, the authors followed the stages of apprehension, synthesis, theorization and recontextualization. Through the process of analysis we can get to the conclusion that there are no ready recipes, even though there are methodological thoughts which direct this practical know how to do. Nevertheless, it is important to consider that part of this crossing over depends on the sensitivity, intuition, shrewdness, astuteness, practice and experience on the investigator to fi nally obtain, the construction of new knowledge that, very soon, will be surpassed by new looks and new recontextualizations.